Simple Formation of Nanostructured Molybdenum Disulfide Thin Films by Electrodeposition - S. K. Ghosh; C. Srivastava; S. Nath; J. P. Celis (International Journal of Electrochemistry)
Nanostructured molybdenum disulfide thin films were deposited on various substrates by direct current (DC) electrolysis form aqueous electrolyte containing molybdate and sulfide ions. Post deposition annealing at higher temperatures in the range 450–700°C transformed the as-deposited amorphous films to nanocrystalline structure. High temperature X-ray diffraction studies clearly recorded the crystal structure transformations associated with grain growth with increase in annealing temperature. Surface morphology investigations revealed featureless structure in case of as-deposited surface; upon annealing it converts into a surface with protruding nanotubes, nanorods, or dumbbell shape nanofeatures. UV-visible and FTIR spectra confirmed about the presence of Mo-S bonding in the deposited films. Transmission electron microscopic examination showed that the annealed MoS2 films consist of nanoballs, nanoribbons, and multiple wall nanotubes.